Super plasticity in a cold-welded Al-Cu joint - Gao, Jing; Wang, Kaifeng; Fu, Xiaoqian; Chen, Sijing; Zhang, Zijiao; Wang, Qiannan; Li, Jingjing; Yu, Qian (Applied physics letters, 2019)
The technology of welding dissimilar metals at the nanoscale is of importance in the fabrication of electronics. In this work, we achieved cold welding of aluminum (Al) and copper (Cu) nanowires by simple mechanical contact without extra heating and/or voltage applied in transmission electron microscopy (TEM). During the welding process, the welding surface gradually disappeared due to the significant inter-diffusion between Al and Cu under a relatively low pressure, which resulted in the formation of an Al/Cu solid solution and Al3Cu2 intermetallic compound. The following in-situ TEM tensile test revealed that the joint displayed super plasticity with a total elongation even beyond 100%. The corresponding plastic deformation was dominated by the partial dislocation glide and grain rotation. Our results not only shed light on developing the advanced welding technology for dissimilar metals at the nanoscale but also improved the understanding of the joint deformation mechanisms.